2019
DOI: 10.1016/j.jinf.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of adult meningitis during antiretroviral therapy scale-up in southern Africa: Results from the Botswana national meningitis survey

Abstract: s u m m a r yObjectives: Data on meningitis epidemiology in high HIV-prevalence African settings following antiretroviral therapy scale-up are lacking. We described epidemiology of adult meningitis in Botswana over a 16-year period. Methods: Laboratory records for adults undergoing lumbar puncture (LP) 20 0 0-2015 were collected, with complete national data 2013-2014. Cerebrospinal fluid (CSF) findings and linked HIV-data were described, and national incidence figures estimated for 2013-2014. Temporal trends i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…We then determined factors associated with CSF viral escape using the following covariates: pleocytosis, CD4+ T-cell count, CSF protein and glucose concentration, duration on ART and the available demographics. Pleocytosis was defined as CSF white cell count (WCC) ≥ 20 cells/mm 3 [ 27 , 28 , 29 ]. The cut-off to identify elevated protein concentration was ≥1 g/L [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…We then determined factors associated with CSF viral escape using the following covariates: pleocytosis, CD4+ T-cell count, CSF protein and glucose concentration, duration on ART and the available demographics. Pleocytosis was defined as CSF white cell count (WCC) ≥ 20 cells/mm 3 [ 27 , 28 , 29 ]. The cut-off to identify elevated protein concentration was ≥1 g/L [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The National Institute for Communicable Diseases (NICD) reported that the CM burden remained high among severely immunosuppressed HIV-positive patients in South Africa despite increased antiretroviral therapy coverage . In Botswana, also in Southern Africa, current adult data show 89% (4432/5004) CM and 8% (382/5004) pneumococcal meningitis, whereas pediatric data show 26.9% (175/651) CM, 18.9% (123/651) S. pneumoniaee , 20.3% (132/651) H. influenzae , and 1.1% (7/651) Mycobacterium tuberculosis . , Progress in meningitis assay development and implementation has been very impressive, here accounting for the capacity to identify emerging CNS pathogens. Two in-house multiplex real-time PCR assays were developed for the detection of S. pneumoniaee , N. meningitidis , H. influenzae , enteroviruses, mumps virus, and herpes simplex virus.…”
Section: Evolution Of Meningitis Pathogens and Laboratory Diagnostic ...mentioning
confidence: 99%
“…18 The proportions of individuals presenting with advanced HIV disease is still reported to be in the range of 20%-35% in recent studies conducted in the southern and east African region, 12,[15][16][17][18] and the overall number of individuals with very low CD4 counts has remained stable for the past decade. 17,19 A further challenge to effective implementation of the WHO AHD package has been the widespread uptake of rapid or same-day ART initiation. 20 With rapid ART initiation, even if baseline CD4 tests are sent, the current turn-around times with flow-cytometry 21 testing in centralized laboratories, which remains the mainstay of CD4 testing in most LMICs, means that ART initiation occurs in most cases before the availability of CD4 results.…”
Section: Introductionmentioning
confidence: 99%